Polarisors: Ultra‐broadband Polarisers Based on Metastable Free‐Standing Aligned Carbon Nanotube Membranes (Advanced Optical Materials 10/2014). Issue 10 (October 2014) - Cole, Matthew T.; Doherty, Matthew; Parmee, Richard; Dawson, Paul; Milne, William I.
<x xml:space="preserve">Abstract</x> On page 929, M. T. Cole et al. demonstrate free‐standing polarisers based on solid‐state extruded multiwalled CNTs. The degree of cohesion within their membranes derives from inter‐tube van der Waals interactions, intimately related to the detailed chemical vapour deposition conditions. The membranes form highly aligned, planar metastable morphologies well‐suited for a range of polariser applications. For the first time, ultra‐broadband polarisation (400 nm–2.5 mm) is demonstrated with the observed transmission corroborated by effective medium and full numerical simulations. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>